The Characteristics and Utilization of Pekarangan Pangan Lestari to Achieve Urban Food Security in Depok City, West Java - Ovita Trianingsih; Ratna Yuniati; Marina Silalahi; Anisa Anggraeni (Journal of Tropical Ethnobiology, 2023)
The main challenge for urban food security is a public policy perspective that considers food security only from a rural lens and agricultural activities in the cities are appraised to have no place. In dealing with that challenge, the local government of Depok City has developed a local urban food system program called Pekarangan Pangan Lestari (P2L) in Bojongsari Sub-district. The existence of P2L influenced the increase of Depok City's food security score by 1.68 within 5 years and placed Depok City as the 10th city with the highest food security index in Indonesia. This study aims to document the characteristics and utilization of P2L in the Bojongsari Sub-district. The research was conducted using in- depth interviews with 30 people and field observation in 33 P2L. The area of Pekarangan Pangan Lestari (P2L) in the Bojongsari Sub-district can be found in the villages of Duren Seribu, Duren Mekar, Pondok Petir, and Serua, is categorized as moderate and narrow, and managed by the Women Farmers group. P2L functions as living barns (lumbung hidup), living stalls (warung hidup), living pharmacies (apotek hidup), nurseries, livestock, and fisheries. A total of 92 species belonging to 86 genera and 47 families were identified in Bojongsari Sub-district. These plants have been used by the society in Bojongsari Sub-district as a source of medicine, vegetables, spices, herbs, vitamins, and carbohydrates as much as 55%, 17%, 10, 9, 8,17, respectively. Besides, there are several animals raised in P2L such as chickens, goats, and catfish.